USE OF MOBILE DEVICES IN LIBRARY BY STUDENTS OF DR. PATANGRAO KADAM MAHAVIDYALAYA, SANGLI (International Journal of Food and Nutritional Sciences, 2022)
In this paper, Bharati Vidyapeeth's Dr. Patangrao Kadam Mahavidyalaya, Sangli Library, an attempt has been made to inform students about the actual use of mobile devices and the usefulness and effectiveness of mobile phones for educational purposes. The findings of this study revealed that most of the respondents use mobile devices for more than 6 hours per day and 80% of the time spent in the library is spent using mobile devices. A smartphone is the most used mobile device. WhatsApp, Instagram, Facebook, and library blog are the most used apps by students. Only 3% of students use mobile for e-journals and e-books. This study concluded that students use mobile devices in the library; they use mobile devices extensively for their daily information needs, entertainment, and communication purposes.